Diagnosis and Management of Wilms Tumor - Nicodemus (Open Access Indonesian Journal of Medical Reviews, 2022)
Wilms Tumor is one of the malignancies frequently found in children under five years old. This tumor is frequently found coincidentally by parents or caregivers who notice a lump in the children’s abdomen. The specific factors of Wilms tumor have not been detected yet. However, it is often associated with specific syndromes as a predisposing factor and a mutation of specific genes. The symptoms caused by this tumor are varied, starting from asymptomatic without any symptom to severe symptoms due to the tumor distribution to the lung. In general, Wilms tumor attacks one of the kidneys (unilateral) with different grades and particular histology. Generally, the management encompasses surgery, chemotherapy, and radiotherapy, depending on the tumor grade. The patients’ recovery rate and managed survival rate were quite high with a low recurrence rate. Therefore, a clinical approach and skepticism of Wilms tumor become one of the diagnoses in children with an abdominal mass.